Associations Between the Continuity of Ambulatory Care of Adult Diabetes Patients in Korea and the Incidence of Macrovascular Complications - Young-Hoon Gong; Seok-Jun Yoon; Hyeyoung Seo; Dongwoo Kim (Korean Society for Preventive Medicine, 2015)
Objectives: The goal of this study was to identify association between the continuity of ambulatory care of diabetes patients in South Korea (hereafter Korea) and the incidence of macrovascular complications of diabetes, using claims data compiled by the National Health Insurance Services of Korea. Methods: This study was conducted retrospectively. The subjects of the study were 43 002 patients diagnosed with diabetes in 2007, who were over 30 years of age, and had insurance claim data from 2008. The macrovascular complications of diabetes mellitus were limited to ischemic heart disease and ischemic stroke. We compared the characteristics of the patients in whom macrovascular complications occurred from 2009 to 2012 to the characteristics of the patients who had no such complications. Multiple logistic regression was used to assess the effects of continuity of ambulatory care on diabetic macrovascular complications. The continuity of ambulatory diabetes care was estimated by metrics such as the medication possession ratio, the quarterly continuity of care and the number of clinics that were visited. Results: Patients with macrovascular complications showed statistically significant differences regarding sex, age, comorbidities, hypertension, dyslipidemia and continuity of ambulatory diabetes care. Visiting a lower number of clinics reduced the odds ratio for macrovascular complications of diabetes. A medication possession ratio below 80% was associated with an increased odds ratio for macrovascular complications, but this result was of borderline statistical significance. Conclusions: Diabetes care by regular health care providers was found to be associated with a lower occurrence of diabetic macrovascular complications. This result has policy implications for the Korean health care system, in which the delivery system does not work properly.